2020
DOI: 10.1111/jcmm.15331
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of laryngeal squamous cell cancer progression by the lncRNA RP11‐159K7.2/miR‐206/DNMT3A axis

Abstract: Laryngeal cancer, more than 95% of which are squamous cell carcinomas (SCC), is the second most common malignant neoplasm in head and neck. Its incidence has remarkably increased over the recent years due to the high smoking rates, industrialization and ageing. 1,2 Despite considerable progress in surgical techniques, as well as chemotherapy and radiotherapy, the prognosis of advanced laryngeal cancer remains poor. [3][4][5] Also, the exact molecular mechanisms underlying the carcinogenesis or progression of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Total RNA from LSCC tissues and cell lines was extracted using Trizol reagent (Invitrogen, Carlsbad, CA, USA) according to the manufacturer’s instructions. The process of qRT-PCR was as previously reported [ 18 ]. Data were calculated using the 2 -ΔΔCt method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA from LSCC tissues and cell lines was extracted using Trizol reagent (Invitrogen, Carlsbad, CA, USA) according to the manufacturer’s instructions. The process of qRT-PCR was as previously reported [ 18 ]. Data were calculated using the 2 -ΔΔCt method.…”
Section: Methodsmentioning
confidence: 99%
“…AMC-HN-8 and TU-212 cells in 24-well plates were transfected with a luciferase reporter and indicated expression constructs. The assays were carried out as previously reported [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Xin Wang et al knocked out the endogenous long noncoding RNA RP11-159K7.2 in TU-212 cells and AMC-HN-8 cells with the CRISPR-Cas9 system. The results showed that RP11-159K7.2 knockout reduced the proliferation and invasion of laryngeal squamous carcinoma cells (LSCC) in vivo and in vitro, suggesting that lncRNA RP11-159K7.2 might be a potential biomarker for LSCC therapy [91]. On the other hand, microRNAs (miRNAs) are attracting increasing attention for their role in cancer progression.…”
Section: Application Of Crispr -Cas9 In Cancer Treatmentmentioning
confidence: 99%
“…Luciferase reporter assay AMC-HN-8 and TU-212 cells in 24-well plates were transfected with a luciferase reporter and indicated expression constructs. The assays were carried out as previously reported [18].…”
Section: Western Blotmentioning
confidence: 99%